Let's evaluate each expression:
-
Expression A: \[ -1.43 + 1.75 = 0.32 \]
-
Expression B: \[ -1.43 - 1.75 = -1.43 - 1.75 = -3.18 \]
-
Expression C: \[ -1.43 + (-1.75) = -1.43 - 1.75 = -3.18 \]
-
Expression D: \[ -1.43 - (-1.75) = -1.43 + 1.75 = 0.32 \]
Now we can compare the results:
- Expression A = 0.32
- Expression B = -3.18
- Expression C = -3.18
- Expression D = 0.32
From this analysis, we have:
- Expression A and Expression D have the same value of 0.32.
- Expression B and Expression C have the same value of -3.18.
Thus, the pairs of expressions that have the same value are:
- Expression A and Expression D
- Expression B and Expression C
The correct answers are: A and D, B and C.